Grafting in Vegetables: Transforming Crop Production with Cutting-Edge Techniques - Mohsin Raza (Kashmir Journal of Science)
Vegetable grafting is the process of removing the stem of a seedling plant and connecting it to the rootstock of another plant, such as wild brinjal or pumpkin. The grafted seedling is cultivated under regulated climate conditions after attachment, it can be sown in a field. It is a basic propagation technique that results in the acquisition of desirable rootstocks to promote vigor, precocity, improved yield and quality, and improved survival in the face of biotic and abiotic stress. Grafting has created new opportunities in organic vegetable cultivation and lessened the need for chemicals to treat soil-borne illnesses. Vegetable farmers and researchers use grafting as a common technique to increase crop resistance or tolerance to biotic and environmental challenges in a variety of crops, including cucurbitaceous and solanaceous crops. It is important to choose rootstock and scion cultivars carefully to prevent any loss. The production of vegetables in a specialized and delicate agricultural environment may be encouraged using grafting technology. It is a substitute tool that is good for sustainable horticulture that requires less input for the agricultural system of the future and quick in situations where breeding methods are comparatively slow. This innovative, environmentally beneficial strategy has also been boosted by developments in robotic and automated grafting. The cost of producing grafted seedlings will go down significantly in the future due to mechanization.